(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The congestion of radio spectrum has led to the development of new wireless technology, Light Fidelity also referred as LIFI, which has a much broader spectrum. LIFI is a technology based on visible light communication (VLC) that makes use of LEDs as a source for data communication. The intensity of LED varies faster than a human eye can follow and helps to transmit the data. Our research deals with the usage of this technology for the future good of the world. A simple experiment to show the transmission of alphanumeric data using visible light communication is carried out. A Led light is the only source to transmit the data from the transmitter end to the receiver’s. A keyboard is being employed as an input for the alphanumeric data and an LCD to display the inputted characters.